How Did the Tripartite Relationship Among the United States, the Soviet Union and Cuba Lead to the Cuban Missile Crisis and Complicate Efforts to Resolve the Crisis? - Sanghro, Rafi Raza; Chandio, Jalil Ahmed; Soomro, Siraj Ahmed; Mahar, Javed Ahmed (Journal of History Culture and Art Research, 2018)
The Washington and Moscow relations deteriorated culminated to the worst during 1962, on the issue of missiles which is commonly known as the Cuban Missile Crisis (CMC) in history. The crisis culminated to the brink of nuclear war between both superpowers. It can be said that it was the part of the Cold War Doctrine in which Cuba played a vital role. It was the head of the Cuba, Mr Fidel Castro who instigated this event which culminated to the brink of the war (nuclear) between the USA and the United Soviets Socialist Republic (USSR). The USSR aim in engaging in the CMC had multi-purposes. The US believed that it would be simple to remove Mr Castro from the political power through various means. However, all the US efforts to remove Castro from the Cuban government failed utterly. Fidel Castro's popularity became more apparent when he sided with the Soviets Union. His government challenged the US and brought the Soviet Union close to pressurise Washington to get a good political deal. This paper, therefore, is designed to understand the political situation of the three countries and their political leadership role in averting the nuclear disaster in the region. Further, it is investigated that to what extent the installation of the Nuclear Missiles in Cuba succumbed to the political disturbance in Washington.